A Numerical Simulation Study of the Migration Law of Water-Sand Two-Phase Flow in Broken Rock Mass. (21st January 2018) - Du, Feng; Jiang, Guanghui; Chen, Zhanqing
Abstract : When the upper parts of coal resources are exploited, the mining overburden separated strata may easily connect with the upper unconsolidated aquifers. This may cause the water-sand two-phase fluids in the aquifers to flow underground through the falling broken rock mass. It has been found that it is difficult to eliminate sand after it has entered a mine, which tends to severely restrict the restorations of mines and causes significant economic losses. This paper studied a seepage system dynamic model of water-sand two-phase fluids in broken rock mass based on related two-phase flow theories. In addition, using FORTRAN language, it established a numerical calculation program to study the migration law of water-sand two-phase fluids flowing into broken rock mass and determined the main influencing factors on the seepage characteristic parameters of water-sand two-phase fluids in broken rock mass and the amounts of sand losses.